1959
DOI: 10.1515/znb-1959-0505
|View full text |Cite
|
Sign up to set email alerts
|

Orientierende Röntgen-Kleinwinkelmessungen an Chloroplasten von Allium porrum

Abstract: Röntgen-Kleinwinkeluntersuchungen an verschiedenen Präparaten der Chloroplasten von Allium porrum haben ergeben:1. Ein gefriergetrocknetes, lipidfreies Präparat zeigte eine diffuse Streuung mit typischem Blättchencharakter. Die Auswertung führt auf zwei Hauptanteile mit Blättchendicken von etwa 250 und 870 A.2. Angetrocknete pulverisierte Chloroplasten lassen einen Bragg schen Reflex bei 62 bis 63 A erkennen. Der starke allgemeine Streuuntergrund macht die Zahlenangaben etwas unsicher.Es liegt nahe, Zusammenhä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The first SAXS experiment on isolated osmium-fixed Aspidistra chloroplasts (Finean et al, 1953) indicated the existence of a structure with a repeat distance of 250 Å, and a similar D R was measured by Kratky et al (1959) for Allium porrum chloroplast pellets. Kreutz et al measured X-ray scattering of the thin layer of dried chloroplast pellets from Antirrhinum majus (Kreutz and Menke, 1960a;Kreutz and Menke, 1960b;Kreutz, 1963b).…”
Section: Plant Thylakoidsmentioning
confidence: 80%
See 3 more Smart Citations
“…The first SAXS experiment on isolated osmium-fixed Aspidistra chloroplasts (Finean et al, 1953) indicated the existence of a structure with a repeat distance of 250 Å, and a similar D R was measured by Kratky et al (1959) for Allium porrum chloroplast pellets. Kreutz et al measured X-ray scattering of the thin layer of dried chloroplast pellets from Antirrhinum majus (Kreutz and Menke, 1960a;Kreutz and Menke, 1960b;Kreutz, 1963b).…”
Section: Plant Thylakoidsmentioning
confidence: 80%
“…Large system inhomogeneity smears peaks and burdens precise structural parameter calculations. Centrifugation, controlled drying (Kratky et al, 1959;Kreutz and Menke, 1960b;Diederichs et al, 1985), or application of an external magnetic field (Geacintov et al, 1972;Sadler, 1976;Nagy et al, 2011;Posselt et al, 2012;Nagy et al, 2013) can be used to increase internal order of the sample during the scattering experiment but might complicate modeling where there typically is an assumption of isotropy and of course also might alter the natural state of the system. Overall, small-angle scattering and microscopy methods complement each other, and their parallel usage is advocated.…”
Section: Scattering Versus Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…A basic assumption in the presented approach is a system consisting of two phases with different average electron density and with sharp interfaces between them [35][36][37]. According to Porod's law, for such a two-phase system the scattering intensity at large q decreases with q 4 (figure 4a and 4b):…”
Section: The Size Of Mineral Particles: T-parametermentioning
confidence: 99%